L’écran de fumée des incendies de la Commune de 1871 - Hélène Lewandowski (Cahiers d’histoire)
History has typically recorded from the latest French revolution of the 19th century that some of the most magnificent monuments of the Parisian heritage were set on fire during the Bloody Week. At that time these burnings were compared to the Apocalypse and the Insurgents who started them to Barbarians decided to bury all signs of civilization. Another reality is concealed behind such an “Official Version”. A civil war took place in Paris which material losses are far exceeding the mere burning of some ten monuments: more than one thousand buildings have been destroyed. If people of today cannot get over the loss of this heritage, once the shock went by the Bourgeois French republic has seized the opportunity to get rid of prestige monuments seen as unnecessary and onerous and prescribe new buildings more adapted to conduct its affairs.